Patrouille op de Singel. Uit: archief F. Domela Nieuwenhuis , VI a I B, no. 26. Originele foto: BG A61/161 - Favier, A.,
Patrouille op de Singel. Uit: archief F. Domela Nieuwenhuis , VI a I B, no. 26. Originele foto: BG A61/161.